Relationship of Red Cell Distribution Width (RDW) To the Results Total Iron Binding Capacity (TIBC) In Chronic Kidney Failure Patients with Anemia: Hubungan Red Cell Distribution Width (RDW) Terhadap Hasil Total Iron Binding Capacity (TIBC) Pada Pasien Gagal Ginjal Kronik Dengan Anemia - Eka Safitri, Devayanti; Woelansari, Evy Diah; Suhariyadi (Universitas Muhammadiyah Sidoarjo, 2022)
Chronic kidney failure is caused by the body's inability to maintain metabolism and fluid balance due to progressive kidney function disorders that will trigger anemia. The cause of anemia in kidney failure is inflammation, which causes inhibition of iron release, resulting in a decrease in iron in the body. Signs of iron deficiency in chronic kidney failure are low levels of Total Iron Binding Capacity (TIBC) and in complete blood count; there is an increase in levels of Red Cell Distribution Width (RDW). This study aims to determine the relationship between Red Cell Distribution Width (RDW) and the results of Total Iron Binding Capacity (TIBC) in patients with chronic kidney failure with anemia. This study was conducted in January-April 2022, using a cross sectional method on 30 samples of patients with chronic kidney failure with anemia by examining a sample of patients at the Haji Regional General Hospital Surabaya. Most of the research results of the research subjects were male (n =16; 53,3%). The normal RDW is 33,3% (10/30), the high RDW is 66,7% (20/30), the low TIBC is 76,7% (23/30), and the normal TIBC is 23,3% (7/30). As much as 53,3% (16/30) for high RDW values with low TIBC. The result of the Pearson correlation test between RDW and TIBC was r = 0.014 (p = 0.940). Therefore, there is no significant relationship between RDW and TIBC in CKD patients with anemia at the Haji Surabaya Hospital.